PROCESS VISUALIZATION SYSTEM ANALYSIS AND APPLICATION OPPORTUNITIES - Dukšta, Gunta; Gaigule, Alla; Šindlers, Vladislavs; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
More and more often personal computers (PC) and their networks are integrated in the automation systems. Usually a task of PC in the automation systems is to ensure automated control of processes, their registration and visualization. Internationally such systems are called SCADA (Supervisory Control and Data Acquisition). The most common principle of process tasks distribution among PLC and PC is as follows – PLC controls and regulates the process, whereas PC registers and performs functions of extended process operator panel. The paper deals with the research and analysis of the process visualization system SCADA and its application in JSC Rēzeknes siltumtīkli to improve the performance quality.